Identification of a HIV-1 circulating BF1 recombinant form (CRF75_BF1) of Brazilian origin that also circulates in Southwestern Europe - Bacqué, Joan; Delgado, Elena; Gil, Horacio; Ibarra, Sofía; Benito, Sonia; García-Arata, Isabel; Moreno-Lorenzo, María; de Adana, Ester Sáez; Gómez-González, Carmen; Sánchez, Mónica; Montero, Vanessa; Thomson, Michael M. (Frontiers in Microbiology, 2023)
Introduction The high recombinogenic potential of HIV-1 has resulted in the generation of countless unique recombinant forms (URFs) and around 120 reported circulating recombinant forms (CRFs). Here we identify through analyses of near full-length genomes (NFLG) a new HIV-1 CRF derived from subtypes B and F1. Methods HIV-1 protease-reverse transcriptase (Pr-RT) sequences were obtained by RT-PCR amplification from plasma RNA. Near full-length genome sequences were obtained after amplification by RT-PCR in 5 overlapping fragments. Phylogenetic sequence analyses were performed via maximum likelihood. Mosaic structures were analyzed by bootscanning and phylogenetic analyses of genome segments. Temporal and geographical estimations of clade emergence were performed with a Bayesian coalescent method. Results Through phylogenetic analyses of HIV-1 Pr-RT sequences obtained by us from samples collected in Spain and downloaded from databases, we identified a BF1 recombinant cluster segregating from previously reported CRFs comprising 52 viruses, most from Brazil (n = 26), Spain (n = 11), and Italy (n = 9). The analyses of NFLG genomes of 4 viruses of the cluster, 2 from Spain and 2 from Italy, allowed to identify a new CRF, designated CRF75_BF1, which exhibits a complex mosaic structure with 20 breakpoints. All 4 patients harboring CRF75_BF1 viruses studied by us had CD4+ T-cell lymphocyte counts below 220/mm3 less than one year after diagnosis, a proportion significantly higher (p = 0.0074) than the 29% found in other patients studied in Spain by us during the same period. The origin of the clade comprising CRF75_BF1 and related viruses was estimated around 1984 in Brazil, with subsequent introduction of CRF75_BF1 in Italy around 1992, and migration from Italy to Spain around 1999. Conclusion A new HIV-1 CRF, designated CRF75_BF1, has been identified. CRF75_BF1 is the 6th CRF of South American origin initially identified in Western Europe, reflecting the increasing relationship of South American and European HIV-1 epidemics. The finding of low CD4+ T-cell lymphocyte counts early after diagnosis in patients harboring CRF75_BF1 viruses warrants further investigation on the virulence of this variant.